Budgeting school operational assistance in Central Java using three spatial process modelling. (May 2019) - Wasono, R; Karim, A; Darsyah, M Y; Suwardi
Abstract: The formulation of Indonesian school operational assistance is a complex issue, as each region has different characteristics. The aim of this research was to find out the mapping of the distribution of school operational assistance budget in Central Java Province, to develop the equalization model of Indonesian school operational assistance of Central Java Province using spatial through three spatial processes namely spatial lag X (SLX), spatial autoregressive (SAR), and spatial error model (SEM). Spatial modeling is expected to be a tool of educational development planning so that the development is more directed to equitable distribution of Indonesian school operational assistance in Central Java. The distribution of funds for the program is one form of government expenditures in the form of subsidies for the education sector as the compensation from reduced subsidies for fuel oil. The research results show that the SEM model is the best model, and the estimation results show that the school development budget, school management and human development index can significantly be a determinant of the distribution of Indonesian school operational assistance.